Improved creep resistance of AZ91 magnesium alloy after the micro arc oxidation process - Selvi, Ekin; Muhaffel, Faiz; Filiz, Halil Ibrahim; Vanli, Ali Serdar; Baydogan, Murat (ELSEVIER SCIENCE SA, 2023)
AZ91 Mg alloy has a wide range of applications in the automotive industry, although its use is restricted to powertrain applications due to its low creep resistance. In this study, the effect of the micro arc oxidation (MAO) coating on the creep resistance of an AZ91 Mg alloy was investigated to take advantage of the coating layer with high thermal insulation properties. In this context, the MAO process was applied to AZ91 Mg alloy using a bipolar pulsed DC power supply. The creep tests were conducted at different temperatures (150-200 degrees C) and stresses (25-90 MPa) for the bare and coated samples, and the minimum creep rates were determined. It has been shown that the MAO coating reduces the creep rate of the bare alloy by 35%-84% depending on the temperature and the stress due to the stress-reducing effect and thermal barrier properties of the MAO coating. Based on the calculated creep activation energy and stress exponents, creep mechanisms were proposed for the bare and coated alloys. Effective activation energy was also calculated and lattice diffusion-controlled dislocation climb was determined to be the effective creep mechanism for both samples at lower stresses, while pipe diffusion controlled dislocation climb was effective at higher stresses.
Keywords: AZ91; Creep; Creep mechanism; Micro arc oxidation; Mg alloy; ELECTROLYTIC OXIDE COATINGS; MECHANICAL-PROPERTIES; CORROSION BEHAVIOR; MICROSTRUCTURE; ALUMINUM; Materials Science